NOVEL GURU ONYEH SEBAGAI METAFORA BAGI KEHIDUPAN MASYARAKAT SASAK - Mulyono, Ana (KOMUNIKE: Jurnal Komunikasi Penyiaran Islam, 2017)
Guru Onyeh novel by Salman Faris is a portrait of the life of the Sasak people depicted through the character of Guru Onyeh who is experiencing social backwardness. Based on this, it can be formulated as follows: (1). How is the image of Guru Onyeh in Guru Onyeh novel by Salman Faris?. (2). How is the struggle of the Sasak people in Guru Onyeh novel by Salman Faris?. (3). How is the life of the Sasak people in Guru Onyeh novel which is a metaphor for the life of the Sasak people in reality?. The purpose of this research are: (1). To describe the figure of Guru Onyeh in Guru Onyeh novel by Salman Faris. (2). To describe the struggle of the Sasak people in Guru Onyeh novel by Salman Faris. (3). To describe the life of the Sasak people in Guru Onyeh novel which is a metaphor of the life of the Sasak people in reality. This research is literature research with qualitative interpretative method. Data are obtained and collected through primary and secondary data sources. The data obtained are explained by descriptive interpretative method. This research uses Charles Sanders Peirce semiotic theory. The results of this study show that the character of Guru Onyeh in the novel has good character. The character description is a diagrammatic icon and an imagi icon (image) that tells the life of the character of Guru Onyeh and describes the character or character of Guru Onyeh. In addition, Guru Onyeh struggle in the novel is a diagrammatic icon and an imagi icon (image) for the struggle to organize the life of the Sasak people. All events or events occurring in Guru Onyeh novel are a metaphorical icon for the life of the Sasak community in the real world. Furthermore, the story of Guru Onyeh novel is an index for the sociocultural life of the Sasak people, that is, the novel story is a sign of real life. In addition, Guru Onyeh novel is a social critique. That is, the novel story comes as a form of criticism against the Sasak community and the ruler.